Chapter Lavoro e welfare oltre la distinzione tra ‘politiche economiche’ e ‘politiche sociali’ - Pennacchi, Laura (Firenze University Press, 2025)
The essay examines the reasons why the neoliberalism, with his dynamics of privatization, has broken the nexus between work and welfare state and the way by which the nexus can be restored beyond the disntinction between economic policies and social policies.